Combining Soft- and Hard-Templating Approaches in MWW-Type Zeolites - Anderson Joel Schwanke; Jaíne Fernandes Gomes; Katia Bernardo-Gusmão; Sibele Pergher (Molecules, 2020)
A combination of hard-templating (HT) and soft-templating (ST) approaches was studied to obtain MWW-type materials with intermediate physicochemical properties. The HT methodology involved the introduction of carbon particles as hard templates during gel synthesis to obtain a layered zeolitic precursor (LZP) with particles possessing a microspherical morphology. The LZP obtained was treated with surfactants as soft templates to expand the layers of the LZP, followed by a pillaring procedure. The materials were characterized by X-ray diffraction, transmission and scanning electron microscopy, elemental analysis and N2 adsorption. The results demonstrate that the obtained material possesses intermediate properties from both approaches, with interparticle mesopores/macropores and pore sizes between 18 and 46 Å. However, the ST procedure causes a partial disruption of some microspheres, forming small crystallite aggregates, and results in a decrease in the number of interparticle mesopores/macropores previously formed by the HT method.